A NOVEL APPROACH: THREE-GROUP EXPLORATION STRATEGY ALGORITHM FOR SOLVING OPTIMIZATION PROBLEMS - Ali, Ayad (Bakti Nusantara Institute, 2025)
In this study, we present a novel optimization technique, known as the Three-Group Exploration Strategy (TGES) algorithm, specifically inspired by collaborative group dynamics often seen in problem-solving. We showed wide testing on 26 widely-recognized benchmark functions, providing a severe comparison between TGES and several well-established optimization algorithms. These results highlight TGES’s effectiveness in finding optimal solutions with high reliability and accuracy. Furthermore, the practical applications of TGES are demonstrated by successfully solving six interesting, real-world engineering problems, showcasing its adaptability and robustness. The experimental results indicate that TGES not only exhibits superior optimization performance, but it also achieves faster convergence and higher solution quality compared to several leading algorithms. This finds TGES algorithm as a strong and adaptable tool for solving a variety of engineering optimization problems.